The characterisation of hibernating myocardium : a study of imaging techniques, histological features and clinical relevance - Gunning, Mark Gerard (Department of Medicine, 2024)
Patients with impaired left ventricular function have a poor prognosis. Those with three vessel coronary artery disease who successfully undergo revascularisation have a better outlook but their peri-operative risk is high. Viable myocardium with impaired coronary flow reserve and impaired contractility recovers function following revascularisation and the preoperative identification of this "hibernating myocardium" helps to select those patients most likely to benefit from surgery. The accurate differentiation of hibernating tissue from full thickness myocardial scar is important as the choice of the correct treatment for patients with or without evidence of hibernation has important prognostic implications. This work comprises five studies which evaluate the comparison of imaging techniques for the identification of myocardial hibernation, the histological features which characterise hibernating tissue when compared to normal myocardium or scar, and the relationship of histology to imaging characteristics, and finally the clinical impact of revascularising hibernating myocardium when compared with medical treatment alone.